2019
DOI: 10.1111/ecog.04704
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐scale drivers of plant trait distributions in a fragmented forest landscape

Abstract: During community assembly, plant functional traits are under selective pressure from processes operating at multiple spatial scales. However, in fragmented landscapes, there is little understanding of the relative importance of local‐, patch‐ and landscape‐scale processes in shaping trait distributions. Here, we investigate cross‐scale influences of landscape change on traits that dictate plant life history strategies in re‐assembling plant communities in a fragmented landscape in eastern China. Using forest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
(137 reference statements)
1
9
0
Order By: Relevance
“…However, few case studies have considered the fragmentation effects at multiple scales together under a hierarchical framework. In the TIL region, we found that plant traits were both affected by cross-scale interactions between the island and landscape features (Jin et al, 2020). Further, by observing interdependent effects at the plot-, island-and landscape-scales, we found that habitat fragmentation's effects were hierarchically structured (Wilson et al, 2020).…”
Section: Special Findings In Til Regionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, few case studies have considered the fragmentation effects at multiple scales together under a hierarchical framework. In the TIL region, we found that plant traits were both affected by cross-scale interactions between the island and landscape features (Jin et al, 2020). Further, by observing interdependent effects at the plot-, island-and landscape-scales, we found that habitat fragmentation's effects were hierarchically structured (Wilson et al, 2020).…”
Section: Special Findings In Til Regionmentioning
confidence: 74%
“…Besides ENN and distance to mainland, distance to the nearest larger island and island shape were also used as the proxies linking to the fragmentation per se at patch scale. Meanwhile, the patch number, patch density, and the relative habitat amount were used to measure the fragmentation degree at the landscape scale in previous studies in the TIL region (Hu et al, 2012;Jin et al, 2020;Wilson et al, 2020).…”
Section: Remote Sensing Data For Quantifying Key Features Of the Central Til Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, much idiosyncrasy remains among studies of functional responses to landscape pattern, whereby the relative importance of ecological processes seems to differ from place to place (Rhodes et al 2008;Morissette et al 2019), and findings from one study do not necessarily apply to others (Randin et al 2006;Lessard et al 2012). Such context-dependency is poorly understood (Shackelford et al 2016;Jin et al 2019), hampering the effective transferability of landscape-scale conservation and management policies (Gilroy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, small-sized plants reflecting postfragmentation recruitment, should show stronger decline (Benítez-Malvido & Martínez-Ramos 2003). This pattern should be particularly the case of mature-forest, shade tolerant species, many of which are especially vulnerable to changes in abiotic factors (e.g., water stress, soil or air humidity or wind damage: Turner 1996, Scariot 1999, Benítez-Malvido & Martínez-Ramos 2003, Lasky et al 2013, Jin et al 2020 and biotic factors such as pollinators and dispersers (e.g., Cordeiro & Howe 2001, Osuri et al 2017. This latter expectation is consistent with documentation of the negative impact of fragmentation on animals that play such roles (e.g., Aguilar et al 2006, Cramer et al 2007, Moran & Catterall 2014.…”
mentioning
confidence: 99%